Nonfamilial cherubism - A Trivedi; S D Gupta; S Sharma; R Mehta (Wolters Kluwer Medknow Publications, 2013)
Cherubism is a non neoplastic progressive heredity disease affecting the jaw bones. It is a benign disease with a characteristic symmetrical involvement of the maxilla and mandible. It usually affects children before 5 years of age, with painless progressive swelling of the cheeks, frequently associated with dental malformations. Here, we are presenting a case report of a 12-year-old boy suffering from cherubism.